2016
DOI: 10.1590/0103-8478cr20150203
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphine, ketoprofen and Arnica montana 6x and 30x per oral transmucosal or subcutaneous route for control of postoperative pain in cats subjected to hysterectomy with bilateral salpingo-oophorectomy

Abstract: Comparison of morphine, ketoprofen and Arnica montana 6x and 30x per oral transmucosal or subcutaneous route for... Ciência Rural, v.46, n.2, fev, 2016. 330Comparison of morphine, ketoprofen and Arnica montana 6x and 30x per oral transmucosal or subcutaneous route for control of postoperative pain in cats subjected to hysterectomy with bilateral salpingo-oophorectomy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
2
0
7
Order By: Relevance
“…Arnica montana is a plant of the Asteraceae family and it has traditionally been used in extracts with antiseptic, anti-inflammatory, antibacterial, antisclerotic, antifungal, decongestant, wound healing and antioxidant properties [5,7] It is suggested that the component responsible for the effects of the plant is helenalin, a sesquiterpene lactone [11] . It has been reported in several studies that helenalin selectively inhibits NF-κB, thereby exhibiting anti-inflammatory effects [15,44,45] .…”
Section: Resultsmentioning
confidence: 99%
“…Arnica montana is a plant of the Asteraceae family and it has traditionally been used in extracts with antiseptic, anti-inflammatory, antibacterial, antisclerotic, antifungal, decongestant, wound healing and antioxidant properties [5,7] It is suggested that the component responsible for the effects of the plant is helenalin, a sesquiterpene lactone [11] . It has been reported in several studies that helenalin selectively inhibits NF-κB, thereby exhibiting anti-inflammatory effects [15,44,45] .…”
Section: Resultsmentioning
confidence: 99%
“…Tornando-se uma via de mão dupla, faz com que os participantes se tornem mais sensíveis, críticos e reflexivos e auxilia na formação de um profissional com maior habilidade e competência na assistência ao paciente. BANERJEE, 2007;KAROW et al;SILVA et al, 2009;IANNITTI et al, 2016), sendo que dois destes foram realizados em animais (CASSU, et al, 2011;RODRIGUES et al, 2016) e o extrato vegetal predominante foi a Arnica montana, porém, apenas um artigo referiu-se a Arnica brasileira (SILVA et al, 2009). Em relação a concentração da Arnica nenhum apresentou a mesma prescrição e posologia, o que impossibilitou a comparação entre estes.…”
Section: Avaliaçãounclassified
“…Dentre os fatores de risco para desenvolvimento da hipertensão arterial sistêmica (HAS), o excesso de peso e a obesidade desempenham importante papel (SOCIEDADE BRASILEIRA DE HIPERTENSÃO, 2016b;RODRIGUES et al, 2016 ). Crianças e adolescentes com sobrepeso evidenciam uma prevalência três vezes superior de HAS do que crianças não obesas.…”
Section: Introductionunclassified
“…A hipertensão arterial (HAS) é uma doença crônica de grande magnitude, multifatorial e multissistêmica, caracterizada por níveis elevados e sustentados de pressão arterial (SOCIEDADE BRASILEIRA DE HIPERTENSÃO, 2016;RODRIGUES et al, 2016). CARDIOLOGIA, 2016;IBIAPINA et al, 2013;CUSTÓDIO, 2011).…”
Section: Introductionunclassified
“…Alguns destes fatores podem ser prevenidos com uma alimentação adequada, atividade física constante e hábito de vida saudável. O controle da HAS através da mudança no estilo de vida, assim como o tratamento farmacológico é importante para que as complicações da doença sejam evitadas, mas há uma difícil adesão ao tratamento devido ao tratamento ser contínuo e permanente, à inexistência de sintomas em muitos casos e a impossibilidade de cura (RODRIGUES et al, 2016;BRITO & BORTOLOTTO, 2011;SOUZA et al, 2010).…”
Section: Introductionunclassified